COEVOLUTION OF ETHNOPSYCHOTYPE AND ETHNOCULTURE AS FACTORS OF PROFESSIONAL SELF-DETERMINATION OF PERSONALITY - Мотрук, Р. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Typology of ethnopsychotypes is resulted in the article according to Yu. Lipa, three-field, pontic, goth, kievo-russon; typology of ethnic sociotypes according to D. Doncov, Yu. Lipa, O. Kulchickiy, V. Lipinskiy – nordian, pontic, dinarian, ostian. Their coevolution is rotined in the process of anthropoand historiogenesis of Ukrainian ethnos taking into account archaetypes of collective unconscious and geopsychical factors of forming of personality.